The usefulness of fermented katuk (Sauropus androgynus) plus bay leaves to modify fat accumulation, cholesterol and chemical composition of broiler meat - Santoso, U.; Fenita, Y.; Kususiyah, K. (Journal of the Indonesian Tropical Animal Agriculture, 2019)
The usefulness of the addition of fermented herbs (katuk/Sauropus androgynusplus bay leaves) onfat accumulation, and chemical, amino acids and fatty acids composition ofbroiler meats was investigated.At 15 days of age, 280female broilers were divided into seven treatments, as follows:T0) the control;T1) broilers were given a ration with 2.5% fermented katuk plus bay leaf mixture formula 1;T2) broilerswere givena ration with 2.5% fermented katuk plus bay leaf mixture formula 2;T3) broilerswere givena ration with2.5% fermented katuk plus bay leaf mixture formula 3;T4) broilers were given a rationswith 5% fermented katuk plus bay leaf mixture formula 1;T5) broilers were givena ration with 5% fermented katuk plus bay leaf mixture formula 2;T6) broilers were givena ration with 5%  fermented katuk plus bay leaf mixture formula 3. The results of this study showed that the administration of fermented herbs to the ration significantly reduced abdominal fat, gizzard fat, total fat deposition, meat fat, and cholesterol contents. Their inclusions changed calcium, iron, moisture, serine, threonine, arginine, valine, lysine, methionine, myristic acid, pentadecanoic acid, palmitic acid, oleic acid, linolenic acid, cis-11,14-eicosadienoic acid, cis-5,8,11,14,17-eicosapentaenoic acid, and n-3 unsaturated fatty acids of female broiler meats. It can be concluded that administration of fermented herbs formula 2 at5% levels producedchicken meat with lowerfat and cholesterol levels, but higher protein, minerals and n-3 unsaturated fatty acidslevels.